2021
DOI: 10.1002/ags3.12433
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative complications after primary tumor resection on survival in patients with incurable stage IV colorectal cancer: A multicenter retrospective cohort study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…After CRC surgery, the incidence of complications was 18%-38% (6)(7)(8)(20)(21)(22). Complications could increase hospital stay and costs (9), furthermore, patients' mental stress would increase, and some complications might be life-threatening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After CRC surgery, the incidence of complications was 18%-38% (6)(7)(8)(20)(21)(22). Complications could increase hospital stay and costs (9), furthermore, patients' mental stress would increase, and some complications might be life-threatening.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found that age, tumor stage and complications were independent factors of OS and DFS as well. The mechanism of complications which worsened the prognosis might be as follows: 1, complications might delay the follow-up chemotherapy of CRC patients, thus affecting OS and DFS (28,29); 2, complications directly caused damage to the patients' organs and inhibition of the adaptive immune response, resulting in malfunction, thus affecting OS and DFS (8,30); and 3, postoperative peritoneal infection enhanced the invasive activity of residual tumor cells after CRC surgery (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These complications were defined as National Cancer Institute Common Terminology Criteria for Adverse Events v3.0 [CTCAE] grade 3 or 4. Major problems were characterized as CTCTAE grades 1 or 2, and patients who had them had a substantially worse prognosis than those who did not (HR1.62, 95% CI1.21-2.18, P<0.01) ( 38 ). As a result, some oncologists advocate using chemotherapy as the first-line treatment option, as they are concerned about the impact of postoperative complications, particularly when patients experience a deteriorating physical condition (e.g., weight loss and malnutrition) after surgery.…”
Section: Risks Of Ptr In Crc Patients With Incurable Metastasesmentioning
confidence: 99%
“…[1][2][3][4] PIC is known to lead to increases in treatment cost and prolonged hospital stays, and the lack of effective adjuvant therapy is often attributed to PICs. 5,6 In addition, there is increasing evidence that PIC is associated with unfavorable long-term outcomes in various malignancies, such as gastric cancer, 7 colorectal cancer, [8][9][10] breast cancer, 11,12 and esophageal cancer. 13 However, there is no consensus regarding the precise mechanism(s) relating poor long-term survival to PICs.…”
Section: Introductionmentioning
confidence: 99%